Functional Genetic Variant of Long Pentraxin 3 Gene Is Associated With Clinical Aspects of Oral Cancer in Male Patients - Yeh, Chia-Ming; Lin, Chiao-Wen; Chuang, Chun-Yi; Liu, Yu-Fan; Chou, Chia-Hsuan; Yang, Shun-Fa; Chen, Mu-Kuan (Frontiers in Oncology, 2019)
Long pentraxin 3 (PTX3) is produced by various cell types and is correlated with tumor progression in various tumor types. However, the clinical significance of PTX3 polymorphisms in oral cancer and their correlation with the risk of cancer are still unclear. In this study, we assessed the influence of PTX3 gene polymorphisms and environmental factors on susceptibility to oral tumorigenesis. We recruited 865 cases with oral cancer and 1,189 controls. Four single-nucleotide variations of the PTX3 gene (rs1840680, rs2305619, rs3816527, and rs2120243) were verified using a real-time polymerase chain reaction in control participants and cases with oral cancer. We found that rs3816527 in smokers was correlated with the development of late-stage cancer (odds ratio [OR], 2.328; 95% confidence interval [CI], 1.078–5.027) and increased lymph node metastasis (OR, 2.152; 95% CI, 1.047–4.422). Moreover, additional bioinformatics analysis results showed that the rs3816527 C allele variant to the A allele exhibited the strongest exonic splicing enhancer activity. In conclusion, our results suggested that PTX3 rs3816527 plays a role in oral cancer development.